Fatwa dan Ayat Ahkam: Analisis Keputusan Ijtima’ Ulama Komisi Fatwa MUI tentang Perampasan Aset Perspektif Tafsir Maqasidi - Baharuddin, Didin; Husin Watimenna (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This article discusses maqasidi's interpretation of the ahkam verses used in the decision of the IV 2012 Ijtima' Ulama of the Indonesian MUI Fatwa Commission regarding the confiscation of assets of perpetrators of criminal acts of corruption, where the results of this ijtima were then discussed again in the decision of the Ijtima' Ulama of the Fatwa Commission Throughout Indonesia VIII, Number 12/Ijtima' Ulama/VIII/2024 concerning review of the draft law regarding confiscation of assets related to criminal acts. This research mainly analyzes the verses used and their relevance to eradicating corruption. To analyze the verses used as the basis for the Fatwa Commission's Ulama Ijtima Decision, researchers used the maqasidi interpretation. The method used in this article is qualitative, in the form of a descriptive analysis of the results of the decision of the IV and VIII Ijtima' Ulama of the Indonesian Fatwa Commission regarding the confiscation of assets of perpetrators of criminal acts of corruption and the review of the draft law regarding the confiscation of assets related to criminal acts. In contrast, secondary data associated with this research is written. The results of this research show the relevance of the verses about eradicating criminal acts of corruption. As for the maqasidi interpretation approach, the use of verses in decisions can be seen from several aspects, namely: first, the text and law depend on the objective, and the MUI decision uses the appropriate verse for the theme to be decided. Second, the text and law depend on the purpose; the MUI uses fiqhiyah rules to strengthen the interpretation of verses and decision arguments. Third, genuinely bringing benefits and preventing damage (Jalbu al-Mashalih wa Dar'u al-Mafasid), MUI is very concerned about efforts to get benefits and to avoid damage. The recommendations in the decisions given prove this. Fourth, considering the legal impacts (I'tibar al-Maalat), the MUI also pays attention to the legal effects that will arise. Therefore, the MUI provides recommendations in the form of mitigation notes for the legal consequences that will occur.